Arabidopsis thaliana Cuticle Composition Contributes to Differential Defense Response to Botrytis cinerea - Aragón, Wendy; Formey, Damien; Aviles-Baltazar, Norma Yaniri; Torres, Martha; Serrano, Mario (Frontiers in Plant Science, 2021)
The chemical composition of a plant cuticle can change in response to various abiotic or biotic stresses and plays essential functions in disease resistance responses. Arabidopsis thaliana mutants altered in cutin content are resistant to Botrytis cinerea, presumably because of increased cuticular water and solute permeability, allowing for faster induction of defense responses. Within this context, our knowledge of wax mutants is limited against this pathogen. We tested the contribution of cuticular components to immunity to B. cinerea using mutants altered in either cutin or wax alone, or in both cutin and wax contents. We found that even all the tested mutants showed increased permeability and reactive oxygen species (ROS) accumulation in comparison with wild-type plants and that only cutin mutants showed resistance. To elucidate the early molecular mechanisms underlying cuticle-related immunity, we performed a transcriptomic analysis. A set of upregulated genes involved in cell wall integrity and accumulation of ROS were shared by the cutin mutants bdg, lacs2-3, and eca2, but not by the wax mutants cer1-4 and cer3-6. Interestingly, these genes have recently been shown to be required in B. cinerea resistance. In contrast, we found the induction of genes involved in abiotic stress shared by the two wax mutants. Our study reveals new insight that the faster recognition of a pathogen by changes in cuticular permeability is not enough to induce resistance to B. cinerea, as has previously been hypothesized. In addition, our data suggest that mutants with resistant phenotype can activate other defense pathways, different from those canonical immune ones.